Self Healing of Precoated AISI 441 for Solid Oxide Fuel Cell Interconnects. (2nd June 2015) - Berger, Robert; Lundberg, Mats W; Westlinder, Jörgen; Holmberg, Håkan
Abstract : Sandvik Materials Technology develops nanocoatings for SOFC stainless steel interconnects. The self-healing properties of cerium cobalt coated AISI441 (EN 1.4509) have been studied. A partially coated sample was oxidized in air at 800°C for a total of 504 hours. Prior to oxidation a focused ion beam (FIB) was used to mill a trench on the uncoated surface to be used as a reference point relative the coated border. A second FIB trench, made after oxidation, revealed that the oxide formed on the uncoated part adjacent to the coated area contained both cobalt and cerium. Cerium was detected with EDS in the surface oxide of the uncoated area as far as 10 µm away from the coated edge, cobalt had diffused even further. These findings are encouraging since they suggests that cracks introduced in the coating during stamping and/or forming, which are usually in the 1-3 µm range, are likely to self- heal (i.e. become enclosed by the forming Co, Mn, Cr-spinel) upon oxidation.